The Decline of Islamic Parties and the Dynamics of Party System in Post-Suharto Indonesia - Nurjaman, Asep (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
This study aims to investigate the decline of Islamic parties in post-Suharto Indonesia and its correlation with changes in the electoral system. Using a mixed method, data on the post-Suharto election was analyzed quantitatively using the Pedersen formula, supplemented with a qualitative review of scholarly sources, such as journals, books, and proceedings. The results showed that the changing electoral system triggered dynamics in the party system, leading to a decline in the number of votes for incumbent parties, particularly Islamic parties. This decline led to electoral volatility, where voters were more willing to switch their support from one party to another. Moreover, the decline of Islamic partiess’ electoral performance prevailed, as they could not reclaim their positions. This study offers insight into the workings of political party systems in developing democracies, showing how modifications to the electoral process can influence the political environment. These results add to the growing body of knowledge on party systems and electoral politics, not only in Indonesia but also in comparable contexts around the globe.